Awareness, perception and barriers to seeking information from online academic databases and medical journals as sources of information - Wong, Li Ping; Mohamad Shakir, Sharina Mahavera; Tong, Wen Ting; Alias, Haridah; Aghamohammadi, Nasrin; Arumugam, Kulenthran (Taylor & Francis, 2018)
Medical students’ use of online medical journals as a source of information is crucial in the learning pathway to become medical doctors. We conducted a cross-sectional survey study among University medical students between December 2012 and March 2013 to assess their awareness, perceived usefulness, practices, and barriers to seeking information from online academic databases and medical journals. The response rate was 67.53%. The majority of the students knew of the availability of online academic databases and medical journals. The mean score for awareness (4.25 of possible 11.0), perceived usefulness (13.95 of possible 33.0), and practice (10.67 of possible 33.0) were low. The mean barrier score toward using online academic databases and medical journals was 25.41 (of possible 45.0). Multivariate findings showed that significant barriers associated with overall usage of online databases and medical journals were 1) not knowing where or how to locate databases and 2) unsureness of using the Boolean operators. Availability of full text subscriptions was found to be an important factor in using online databases. Study findings highlighted the need to increase awareness of academic databases’ availability and increase training on ways to search online academic databases and medical journals.